The Risk Factors of Knee Osteoarthritis in Haji General Hospital of Surabaya - Lainjong, Erfan AR; Wahyuni, Chatarina Umbul; Isfandiari, Muhammad Atoillah (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
-